Attention to voices is increased in non-clinical auditory verbal hallucinations irrespective of salience. (12th November 2021) - Castiajo, Paula; Pinheiro, Ana P.
Abstract: Alterations in the processing of vocal emotions have been associated with both clinical and non-clinical auditory verbal hallucinations (AVH), suggesting that changes in the mechanisms underpinning voice perception contribute to AVH. These alterations seem to be more pronounced in psychotic patients with AVH when attention demands increase. However, it remains to be clarified how attention modulates the processing of vocal emotions in individuals without clinical diagnoses who report hearing voices but no related distress. Using an active auditory oddball task, the current study clarified how emotion and attention interact during voice processing as a function of AVH proneness, and examined the contributions of stimulus valence and intensity. Participants with vs. without non-clinical AVH were presented with target vocalizations differing in valence (neutral; positive; negative) and intensity (55 decibels (dB); 75 dB). The P3b amplitude was larger in response to louder ( vs. softer) vocal targets irrespective of valence, and in response to negative ( vs. neutral) vocal targets irrespective of intensity. Of note, the P3b amplitude was globally increased in response to vocal targets in participants reporting AVH, and failed to be modulated by valence and intensity in these participants. These findings suggest enhanced voluntary attention to changes in vocal expressions but reduced discrimination of salient and non-salient cues. A decreased sensitivity to salience cues of vocalizations could contribute to increased cognitive control demands, setting the stage for an AVH. Highlights: The P3b revealed how attention to vocal emotions is affected by AVH proneness. The P3b to vocal targets was increased in AVH-prone subjects irrespective of salience. Selective attention to voices is less sensitive to salience cues as a function of AVH proneness.